The Implementation of the Protection Policy for Children and Women - Jumanah; Annida, Nur Annida Rahmawati; Kesuma, Bimantara Arya; Aldiansyah; Aprianti, Dea Putri (Universitas Muhammadiyah Malang, 2024)
Sexual violence against children is one of the serious problems facing the government today. Socially child protection is a joint effort and action from all social strata, different positions and different roles. They are very aware of the importance of children for the future of the homeland and the nation. As a young generation who have high aspirations for the country, future leaders of the country, and a source of hope for the previous generation, they need the widest possible opportunity to grow and develop mentally, physically and physically. This research approach uses descriptive or data collection using published or perish databases from Google Scholar to produce 640 documents. UU no. 23 of 2002 concerning Child Protection also explains that Child Protection is all activities to guarantee children and their rights so that they can live, grow, develop and participate optimally in accordance with human dignity and status and receive protection from violence and discrimination. But unfortunately in its application often experience obstacles and obstacles, both caused by internal factors and external factors. This can be seen from the increase in cases of child abuse which are increasing every year. The issued policies are hampered in terms of implementation, even though several bodies have been formed such as KPAI (Indonesian National Commission for Child Protection) and P2TP2A.